Proof by Mathematical Induction


Using the principle to proof by mathematical induction we need to follow the techniques and steps exactly as shown.

We note that a prove by mathematical induction consists of three steps.

• Step 1. (Basis) Show that P(n₀) is true.

• Step 2. (Inductive hypothesis). Write the inductive hypothesis: Let k be an integer such that k ≥ n₀ and P(k) be true.

• Step 3. (Inductive step). Show that P(k + 1) is true. 

In mathematical induction we can prove an equation statement where infinite number of natural numbers exists but we don’t have to prove it for every separate numbers. 

We use only two steps to prove it namely base step and inductive step to prove the whole statement for all the cases. Practically it’s not possible to prove a mathematical statement or formula or equation for all the natural numbers but we can generalize the statement by proving with induction method. As if the statement is true for P (k), it will be true for P (k+1), so if it is true for P (1) then it can be proved for P (1+1) or P (2) similarly for P (3), P (4) and so on up to n natural numbers.

In Proof by mathematical induction the first principle is if the base step and inductive step are proved then P (n) is true for all natural numbers. In inductive step we need to assume P (k) is true and this assumption is called as induction hypothesis. By using this assumption we prove P (k+1) is true. While proving for the base case we can take P (0) or P (1).

Proof by mathematical induction uses deductive reasoning not inductive reasoning. An example of deductive reasoning: All trees have leaves. Palm is a tree. Therefore Palm must have leaves.

When the proof by mathematical induction for a set of countable inductive set is true for all numbers it is called as Weak Induction. This is normally used for natural numbers. It is simplest form of mathematical induction where the base step and inductive step are used to prove a set.

In Reverse Induction assumption is made to prove a negative step from inductive step. If P (k+1) is assumed to be true as induction hypothesis we prove P (k) is true. These steps are reverse to weak induction and this is also applicable for countable sets. From this it can be proved that the set is true for all numbers ≤ n and so the proof ends for 0 or 1 which is base step for weak induction.

Strong Induction is similar to weak induction. But for strong induction in inductive step we assume all P (1), P (2), P (3) …... P (k) are true to prove P (k+1) is true. When weak induction fails to prove a statement for all the cases we use strong induction. If a statement is true for weak induction, it is obvious that it is true for weak induction also.


Questions with solutions to Proof by Mathematical Induction

1. Let a and b be arbitrary real numbers. Using the principle of mathematical induction, prove that
(ab)n = anbn for all n ∈ N.

Solution:

Let the given statement be P(n). Then,

P(n): (ab)n = anbn.

When = 1, LHS = (ab)1 = ab and RHS = a1b1 = ab

Therefore LHS = RHS.

Thus, the given statement is true for n = 1, i.e., P(1) is true.

Let P(k) be true. Then,

P(k): (ab)k = akbk.

Now, (ab)k + 1 = (ab)k (ab)

                             = (akbk)(ab) [using (i)]

                              = (ak ∙ a)(bk ∙ b) [by commutativity and associativity of multiplication on real numbers]

                              = (ak + 1 ∙ bk + 1 ).

Therefore P(k+1): (ab)k + 1 = ((ak + 1 ∙ bk + 1)

⇒ P(k + 1) is true, whenever P(k) is true.

Thus, P(1) is true and P(k + 1) is true, whenever P(k) is true.

Hence, by the principle of mathematical induction, P(n) is true for all n ∈ N.



More examples to Proof by Mathematical Induction

2. Using the principle of mathematical induction, prove that (xn - yn) is divisible by (x - y)for all n ∈ N.

Solution:

Let the given statement be P(n). Then,

P(n): (xn - yn) is divisible by (x - y).

When n = 1, the given statement becomes: (x1 - y1) is divisible by (x - y), which is clearly true.

Therefore P(1) is true.

Let p(k) be true. Then,

P(k): xk - yk is divisible by (x-y).

Now, xk + 1 - yk + 1 = xk + 1 - xky - yk + 1

                              [on adding and subtracting x)ky]

= xk(x - y) + y(xk - yk), which is divisible by (x - y) [using (i)]

⇒ P(k + 1): xk + 1 - yk + 1is divisible by (x - y)

⇒ P(k + 1) is true, whenever P(k) is true.

Thus, P(1) is true and P(k + 1) is true, whenever P(k) is true.

Hence, by the Principal of Mathematical Induction, P(n) is true for all n ∈ N.


3. Using the principle of mathematical induction, prove that
a + ar + ar2 + ....... + arn – 1 = (arn – 1)/(r - 1) for r > 1 and all n ∈ N.

Solution:

Let the given statement be P(n). Then, 

P(n): a + ar + ar2 + ….... +arn - 1 = {a(rn -1)}/(r - 1). 

When n = 1, LHS = a and RHS = {a(r1 - 1)}/(r - 1) = a 

Therefore LHS = RHS. 

Thus, P(1) is true. 

Let P(k) be true. Then, 

P(k): a + ar + ar2 + …… + ark - 1 = {a(rk - 1)}/(r - 1) 

Now, (a + ar + ar2 + …... + ark - 1) + ark = {a(rk - 1)}/(r - 1) + ar2                                                                      ....... [using(i)] 
                             = a(rk + 1 - 1)/(r - 1). 

Therefore,
P(k + 1): a + ar + ar2 + …….. +ark - 1 + ark = {a(rk + 1 - 1)}/(r - 1) 

⇒ P(k + 1)is true, whenever P(k) is true. 

Thus, P(1) is true and P(k + 1) is true, whenever P(k) is true. 

Hence, by the principle of mathematical induction, P(n) is true for all n ∈ N. 



Proof by Mathematical Induction

4. Let a and b be arbitrary real numbers. Using the principle of mathematical induction, prove that 
(ab)n = anbn for all n ∈ N.

Solution:

Let the given statement be P(n). Then, 

P(n): (ab)n = anbn

When = 1, LHS = (ab)1 = ab and RHS = a1b1 = ab

Therefore LHS = RHS. 

Thus, the given statement is true for n = 1, i.e., P(1) is true. 

Let P(k) be true. Then, 

P(k): (ab)k = akbk

Now, (ab)k + 1 = (ab)k (ab) 

                      = (akbk)(ab) [using (i)] 

                      = (ak ∙ a)(bk ∙ b) [by commutativity and associativity of multiplication on real numbers] 

                      = (ak + 1 ∙ bk + 1 ). 

Therefore P(k+1): (ab)k + 1 = ((ak + 1 ∙ bk + 1

⇒ P(k + 1) is true, whenever P(k) is true. 

Thus, P(1) is true and P(k + 1) is true, whenever P(k) is true. 

Hence, by the principle of mathematical induction, P(n) is true for all n ∈ N.



More examples to Proof by Mathematical Induction

5. Using the principle of mathematical induction, prove that (xn - yn) is divisible by (x - y)for all n ∈ N.

Solution:

Let the given statement be P(n). Then, 

P(n): (xn - yn) is divisible by (x - y). 

When n = 1, the given statement becomes: (x1 - y1) is divisible by (x - y), which is clearly true. 

Therefore P(1) is true. 

Let p(k) be true. Then, 

P(k): xk - yk is divisible by (x-y). 

Now, xk + 1 - yk + 1 = xk + 1 - xky - yk + 1

                              [on adding and subtracting x)ky] 

= xk(x - y) + y(xk - yk), which is divisible by (x - y) [using (i)] 

⇒ P(k + 1): xk + 1 - yk + 1is divisible by (x - y) 

⇒ P(k + 1) is true, whenever P(k) is true. 

Thus, P(1) is true and P(k + 1) is true, whenever P(k) is true. 

Hence, by the Principal of Mathematical Induction, P(n) is true for all n ∈ N. 


6. Using the principle of mathematical induction, prove that (102n - 1 + 1) is divisible by 11 for all n ∈ N.

Solution: 

Let P (n): (102n – 1 + 1) is divisible by 11. 

For n=1, the given expression becomes {10(2 × 1 - 1) + 1} = 11, which is divisible by 11. 

So, the given statement is true for n = 1, i.e., P (1) is true. 

Let P(k) be true. Then, 

P(k): (102k - 1 + 1) is divisible by 11

⇒ (102k - 1 + 1) = 11 m for some natural number m. 

Now, {102(k - 1) - 1 + 1} = (102k + 1 + 1) = {102 ∙ 10(2k - 1)+ 1} 

                              = 100 × {102k - 1+ 1 } - 99

                              = (100 × 11m) - 99

                              = 11 × (100m - 9), which is divisible by 11

⇒ P (k + 1): {102(k + 1) - 1 + 1} is divisible by 11

⇒ P (k + 1) is true, whenever P(k) is true. 

Thus, P (1) is true and P(k + 1) is true , whenever P(k) is true. 

Hence, by the principle of mathematical induction, P(n) is true for all n ∈ N.


7. Using the principle if mathematical induction, prove that (7n – 3n) is divisible by 4 for all n ∈ N.

Solution: 

Let P(n) : (7n – 3n) is divisible by 4. 

For n = 1, the given expression becomes (7 1 - 3 1) = 4, which is divisible by 4. 

So, the given statement is true for n = 1, i.e., P(1) is true. 

Let P(k) be true. Then, 

P(k): (7k - 3k) is divisible by 4. 

⇒ (7k - 3k) = 4m for some natural number m. 

Now, {7(k + 1) - 3 (k + 1)} = 7(k + 1) – 7 ∙ 3k + 7 ∙ 3k - 3 (k + 1) 
                                           (on subtracting and adding 7 ∙ 3k) 

                              = 7(7k - 3k) + 3 k (7 - 3) 

                              = (7 × 4m) + 4 ∙ 3k

                              = 4(7m + 3k), which is clearly divisible by 4. 

∴ P(k + 1): {7(k + 1) - 3 (k + 1)} is divisible by 4. 

⇒ P(k + 1) is true, whenever P(k) is true. 

Hence, by the principle of mathematical induction, P(n) is true for all n ∈ N. 



Solved examples to Proof by Mathematical Induction

8. Using the principle if mathematical induction, prove that
(2 ∙ 7n + 3 ∙ 5n - 5) is divisible by 24 for all n ∈ N.

Solution: 

Let P(n): (2 ∙ 7n + 3 ∙ 5n - 5) is divisible by 24. 

For n = 1, the given expression becomes (2 ∙ 71 + 3 ∙ 51 - 5) = 24, which is clearly divisible by 24. 

So, the given statement is true for n = 1, i.e., P(1) is true. 

Let P(k) be true. Then, 

P(k): (2 ∙ 7n + 3 ∙ 5n - 5) is divisible by 24. 

⇒ (2 ∙ 7n + 3 ∙ 5n - 5) = 24m, for m = N

Now, (2 ∙ 7k + 1 + 3 ∙ 5k + 1 - 5) 

                       = (2 ∙ 7k ∙ 7 + 3 ∙ 5k ∙ 5 - 5) 

                       = 7(2 ∙ 7+ 3 ∙ 5k - 5) - 6 ∙ 5k + 30

                       = (7 × 24m) - 6(5k - 5) 

                       = (24 × 7m) - 6 × 4p, where (5k - 5) = 5(5k - 1 - 1) = 4p
[Since (5k - 1 - 1) is divisible by (5 - 1)] 

                       = 24 × (7m - p) 

                       = 24r, where r = (7m - p) ∈ N 

⇒ P (k + 1): (2 ∙ 7k + 1 + 3 ∙ 5k + 1 - 5) is divisible by 24.

⇒ P(k + 1) is true, whenever P(k) is true. 

Thus, P(1) is true and P(k + 1) is true, whenever P(k) is true. 

Hence, by the principle of mathematical induction, P(n) is true for all n ∈ 

 Mathematical Induction

Mathematical Induction

Problems on Principle of Mathematical Induction

Proof by Mathematical Induction

Induction Proof




11 and 12 Grade Math 

From Proof by Mathematical Induction to HOME PAGE




Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.



New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.




Share this page: What’s this?

Recent Articles

  1. Quarter Past and Quarter To | Quarter Past Hour | Quarter to Next Hour

    Nov 23, 24 03:45 PM

    Quarter Past and Quarter To
    The hands of clock move from left to right. This is called the clock wise motion. When the minute hand is on the right side of the clock, it shows the number of minutes past the hour. When the minute…

    Read More

  2. Half Past an Hour | What does Half Past Mean? | Half an Hour|Half Past

    Nov 23, 24 03:14 PM

    Half Past 1
    We learnt that, one hour is equal to 60 minutes. When one hour is divided into two, it is half an hour or 30 minutes. The minute hand points at 6. We say, 30 minutes past an hour or half past an hour…

    Read More

  3. Telling the Time | Teaching Time | Analogue Clock| Reading Time

    Nov 23, 24 02:51 PM

    Wall Clock
    Teaching time is an interactive activity for telling time. This activity helps students to learn how to read the clock to tell time using the analogue clock. While reading or observing the time on a

    Read More

  4. 2nd Grade Fractions Worksheet | Basic Concept of Fractions | Answers

    Nov 23, 24 12:22 AM

    Divide the Collection into 4 Equal Parts
    In 2nd Grade Fractions Worksheet we will solve different types of problems on fractions, one-whole, one-half, one-third, one-fourth, three-fourth or s quarter. In a fraction, it is important that the…

    Read More

  5. Time Duration |How to Calculate the Time Duration (in Hours & Minutes)

    Nov 22, 24 12:34 AM

    Time Duration Example
    Time duration tells us how long it takes for an activity to complete. We will learn how to calculate the time duration in minutes and in hours. Time Duration (in minutes) Ron and Clara play badminton…

    Read More